2021
DOI: 10.3390/biomedicines9111723
|View full text |Cite
|
Sign up to set email alerts
|

Association of Mutations Identified in Xanthinuria with the Function and Inhibition Mechanism of Xanthine Oxidoreductase

Abstract: Xanthine oxidoreductase (XOR) is an enzyme that catalyzes the two-step reaction from hypoxanthine to xanthine and from xanthine to uric acid in purine metabolism. XOR generally carries dehydrogenase activity (XDH) but is converted into an oxidase (XO) under various pathophysiologic conditions. The complex structure and enzymatic function of XOR have been well investigated by mutagenesis studies of mammalian XOR and structural analysis of XOR–inhibitor interactions. Three XOR inhibitors are currently used as hy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 113 publications
0
5
0
Order By: Relevance
“…Xanthine oxidase is an important enzyme in purine metabolism and is a form of xanthine oxidoreductase [ 49 ]. The role of xanthine oxidase in the development of gout is well established, as it plays an important role in catalyzing the oxidative hydroxylation of hypoxanthine to xanthine and further catalyzing the production of uric acid (UA) from xanthine [ 50 ].…”
Section: Oxidative Stressmentioning
confidence: 99%
“…Xanthine oxidase is an important enzyme in purine metabolism and is a form of xanthine oxidoreductase [ 49 ]. The role of xanthine oxidase in the development of gout is well established, as it plays an important role in catalyzing the oxidative hydroxylation of hypoxanthine to xanthine and further catalyzing the production of uric acid (UA) from xanthine [ 50 ].…”
Section: Oxidative Stressmentioning
confidence: 99%
“…As an example of the complete inhibition of XOR, consider the metabolism in the case of XOR deficiency, in which the patient has significantly reduced serum uric acid levels and urinary uric acid excretion accompanied by increased urinary xanthine levels ( 40 ). This results in xanthinuria and xanthine stones but no other severe symptoms ( 41 , 42 , 43 ). Plasma hypoxanthine levels, on the other hand, are not significantly increased, due to salvage by HGPRT ( Fig.…”
Section: Discussionmentioning
confidence: 99%
“…We identified two missense variants in XDH (XDH:c.2042C>T, XDH:c.3367G>A) and both are located in the highly conserved aldehyde oxidase/XDH, a/b hammerhead domain of MOCO (Sekine et al, 2021). The MOCO domain catalyses the hydroxylation of hypoxanthine to xanthine to uric acid (Okamoto et al, 2004), and functional studies have demonstrated that variants in this domain affect XDH/xanthine oxidase activity (Kudo et al, 2008; Peretz et al, 2021).…”
Section: Gene Polymorphism (Genomic Dna)a Polymorphism (Genomic Dna)b...mentioning
confidence: 99%